Analysis of Service Quality and Sales Promotion on Consumer Decisions in Using the Grab Bike Application - Sri Rezeki; Agus Rahmadsyah (Outline Publisher, 2023)
This study aims to determine the effect of Service Quality on Decisions to Use on Grab Bikes, determine the effect of Sales Promotion on Decisions to Use on Grab Bikes, determine the effect of Service Quality and Sales Promotion on Decisions to Use on Grab Bikes. The population in this study were all students of STIE Eka Prasetya as many as 1,122 students from 2017 to 2020. Using the Slovin formula with an error rate of 10%, the total sample size was 92 respondents. The results of the study show that Service Quality and Sales Promotion partially have a positive and significant effect on the Decision to Use Grab Bike consumers. The results of the study show that Service Quality and Sales Promotion simultaneously have a positive and significant effect on the Decision to Use Grab Bike consumers. The results of this study are supported by the value of R square (R2) which means that Service Quality and Sales Promotion have an influence on the Decision to Use. While the rest is influenced by other factors that come from outside this research model such as advertising, consumer behavior, satisfaction, loyalty, price and other variables.